2022
DOI: 10.1136/bmjgh-2022-009365
|View full text |Cite
|
Sign up to set email alerts
|

mHealth-community health worker telemedicine intervention for surgical site infection diagnosis: a prospective study among women delivering via caesarean section in rural Rwanda

Abstract: BackgroundSurgical site infections (SSIs) cause a significant global public health burden in low and middle-income countries. Most SSIs develop after patient discharge and may go undetected. We assessed the feasibility and diagnostic accuracy of an mHealth-community health worker (CHW) home-based telemedicine intervention to diagnose SSIs in women who delivered via caesarean section in rural Rwanda.MethodsThis prospective cohort study included women who underwent a caesarean section at Kirehe District Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The included studies were published from 2014 to 2023. A total of 10 studies were conducted at Kirehe District Hospital, 1 , 9 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 two studies at University Teaching Hospital of Kigali, 10 , 22 and one study at University Teaching Hospital of Butare, 23 Kibungo District Hospital, 24 Ruhengeri Referral Hospital, 25 Kabgayi Hospital 14 and Bushenge Provincial Hospital each. 26 Nine studies were cohort studies, 1 , 9 , 15 , 16 , 17 , 19 , 20 , 21 , 24 six were randomized controlled trials 10 , 13 , 18 , 22 , 25 , 26 and two were cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were published from 2014 to 2023. A total of 10 studies were conducted at Kirehe District Hospital, 1 , 9 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 two studies at University Teaching Hospital of Kigali, 10 , 22 and one study at University Teaching Hospital of Butare, 23 Kibungo District Hospital, 24 Ruhengeri Referral Hospital, 25 Kabgayi Hospital 14 and Bushenge Provincial Hospital each. 26 Nine studies were cohort studies, 1 , 9 , 15 , 16 , 17 , 19 , 20 , 21 , 24 six were randomized controlled trials 10 , 13 , 18 , 22 , 25 , 26 and two were cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies were conducted at Kirehe District Hospital, 1 , 9 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 two studies at University Teaching Hospital of Kigali, 10 , 22 and one study at University Teaching Hospital of Butare, 23 Kibungo District Hospital, 24 Ruhengeri Referral Hospital, 25 Kabgayi Hospital 14 and Bushenge Provincial Hospital each. 26 Nine studies were cohort studies, 1 , 9 , 15 , 16 , 17 , 19 , 20 , 21 , 24 six were randomized controlled trials 10 , 13 , 18 , 22 , 25 , 26 and two were cross‐sectional studies. 14 , 23 Five studies had sample sizes above 650 participants 9 , 13 , 16 , 21 , 26 while 12 studies had sample sizes below 650 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last eight years, our research team has explored several strategies for sustainable, home-based, CHW-supported care for women after cesarean delivery in rural Rwanda. We have demonstrated that home-based follow-up by CHWs is feasible and acceptable [5,6], but our attempts for simple clinical screenings or sending pictures to general practitioners has resulted in low SSI diagnostic accuracy [5][6][7][8]. In contrast, our machine learning image-based diagnostic algorithms are yielding higher accuracy: 81.3% sensitivity and 65.3% specificity for visible image algorithms [9], increasing to 97% sensitivity and 87% specificity when using computer vision techniques and color calibration in the image processing pipeline, and 95% specificity and 84% specificity for thermal image algorithms [10].…”
mentioning
confidence: 93%